Indoor Localization and Guidance using Augmented Reality Toolbox - Mohd Zamri, Muhammad Adib Idzam (Universiti Teknologi PETRONAS, 2017)
In this era, new technology were used to ease user. Outdoor guidance uses Global Positioning System (GPS) to pin point one’s location and also and navigate him through the map which downloaded from the Internet. Even so, outdoor guidance is not effectively to apply to indoor guidance. The prime objective of this project is to develop localized indoor guidance system which run in Augmented Reality (AR) mode. AR will provide necessary information by overlaying them on the actual environment captured by camera mounted on a smart glasses and able user to guide through a specific place. Microcontroller Raspberry Pi is used to process the whole system. Instead just showing user the directions, this project also focuses on embedded information on the markers that generate AR images.